Stabilization of dhurrin biosynthetic enzymes from Sorghum bicolor using a natural deep eutectic solvent. (February 2020) - Knudsen, Camilla; Bavishi, Krutika; Viborg, Ketil Mathiasen; Drew, Damian Paul; Simonsen, Henrik Toft; Motawia, Mohammed Saddik; Møller, Birger Lindberg; Laursen, Tomas
Abstract: In recent years, ionic liquids and deep eutectic solvents (DESs) have gained increasing attention due to their ability to extract and solubilize metabolites and biopolymers in quantities far beyond their solubility in oil and water. The hypothesis that naturally occurring metabolites are able to form a natural deep eutectic solvent (NADES), thereby constituting a third intracellular phase in addition to the aqueous and lipid phases, has prompted researchers to study the role of NADES in living systems. As an excellent solvent for specialized metabolites, formation of NADES in response to dehydration of plant cells could provide an appropriate environment for the functional storage of enzymes during drought. Using the enzymes catalyzing the biosynthesis of the defense compound dhurrin as an experimental model system, we demonstrate that enzymes involved in this pathway exhibit increased stability in NADES compared with aqueous buffer solutions, and that enzyme activity is restored upon rehydration. Inspired by nature, application of NADES provides a biotechnological approach for long-term storage of entire biosynthetic pathways including membrane-anchored enzymes. Graphical abstract: Formation of natural deep eutectic solvents in Sorghum bicolor as a stabilizing micro-environment for biosynthetic enzymes and metabolites. Image 10733 Highlights: NADESs provide an inert environment for the dhurrin biosynthetic enzymes in vitro . Enzymes stored in high NADES concentrations are resilient to heat and dehydration stress. Enzyme activity is restored upon rehydration by addition of aqueous buffer.